2004
DOI: 10.1038/sj.onc.1208077
|View full text |Cite
|
Sign up to set email alerts
|

The road to Src

Abstract: More than a quarter of a century has elapsed since the identification of the c-src proto-oncogene. During that period, we have learned that cancer arises as the result of mutations in proto-oncogenes and tumor suppressor genes, and we are now seeing the first fruits of these discoveries, in the form of targeted therapies directed against activated tyrosine kinases such as Bcr-Abl, c-Kit and the EGF receptor. But the discovery of the c-src proto-oncogene was in turn based on decades of study on an avian RNA tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
111
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(112 citation statements)
references
References 87 publications
1
111
0
Order By: Relevance
“…The coupling between the SH2 and SH3 domains is the key to this intersite communication in Src and underlies the importance of the phosphotyrosine-SH2 linkage at the base of the distal surface of the kinase domain. If this linkage is broken, as in the form of the protein produced by the v-Src oncogene, the kinase activity of Src is turned on constitutively (67). The molecular dynamics simulations show that the residues in the SH2 domain that interact with the phosphotyrosine residue in the tail move significantly when the activation loop in the kinase domain is displaced.…”
Section: Dynamics Of the Src Tyrosine Kinasesmentioning
confidence: 99%
See 1 more Smart Citation
“…The coupling between the SH2 and SH3 domains is the key to this intersite communication in Src and underlies the importance of the phosphotyrosine-SH2 linkage at the base of the distal surface of the kinase domain. If this linkage is broken, as in the form of the protein produced by the v-Src oncogene, the kinase activity of Src is turned on constitutively (67). The molecular dynamics simulations show that the residues in the SH2 domain that interact with the phosphotyrosine residue in the tail move significantly when the activation loop in the kinase domain is displaced.…”
Section: Dynamics Of the Src Tyrosine Kinasesmentioning
confidence: 99%
“…The Src tyrosine kinases are a family of closely related proteins that transmit signals initiated by growth factor receptors in human cells (67). A mutant and constitutively activated form of Src is encoded by the first oncogene to be discovered (v-Src; so named for the sarcomas caused by the expression of this retroviral gene).…”
Section: Dynamics Of the Src Tyrosine Kinasesmentioning
confidence: 99%
“…The main differences found among the SJ-1-SJ-5 genomes were the insertion site and the length of the v-src oncogene. The v-src oncogenes in SJ-1 and SJ-2 encoded a p60 v-src protein with a deletion mutation of Tyr527 and downstream amino acids compared with p60 c-src , which appeared to be crucial for transforming activity, as described previously (Martin, 2001(Martin, , 2004Wyke, 1983). Sequence analysis also revealed that the SJ-3, SJ-4 and SJ-5 viral genomes did not directly express the Src oncoprotein.…”
Section: Alv-j-associated Viruses Carrying V-src In Chickensmentioning
confidence: 91%
“…[6][7][8] Huebner and Todaro proposed that all animal cells contain viral "oncogenes" that are transmitted to progeny cells in a repressed form as "proto-oncogenes." 5,9,10 The cellular version of v-Src was confirmed by seminal work carried out by the groups of Varmus, Bishop, Cooper, and Hanafusa. [11][12][13][14] Proto-oncogenes, exemplified by Src, can cause cancer when altered by physical or chemical agents.…”
Section: Src and Cancermentioning
confidence: 92%
“…[16][17][18][19] However, unlike v-Src, c-Src has low transforming ability unless it is overexpressed and/or mutated. 10 As with most tumor cells, Srctransformed cells display characteristic phenotypes that include rounded morphology, increased motility, uncontrolled proliferation, anchorage independence, and growth factor independence. Furthermore, Src leads to the disruption of the actin cytoskeleton as well as cell-cell and cell-matrix adhesions.…”
Section: Src and Cancermentioning
confidence: 99%